Clinical and genetic analyses of APMR4 syndrome caused by novel biallelic LSS variants - Kang, Qingyun; Kang, Hui; Tang, Jingwen; Wang, Miao; Jiang, Haojiang; Ning, Zeshu; Wu, Liwen (Frontiers in Neuroscience, 2024)
Alopecia intellectual disability syndromes 4 (APMR4) caused by Lanosterol synthase (LSS) gene variants is a very rare autosomal recessive neuroectodermal syndrome. It is characterized by congenital alopecia and variable degrees of intellectual disability (ID), frequently associated with developmental delay (DD) and epilepsy. Currently, only three studies regarding LSS-related APMR4 have been reported, the pathogenesis of APMR4 is poorly understood. We studied one patient with LSS-related APMR4 who presented with severe intellectual disability, alopecia, early-onset epilepsy and developmental delay. She is absence of hair on the eyebrows, eyelashes, and scalp. Two novel LSS variants ( c.401T > G and c.369C > G) were detected with whole-exome sequencing(WES). Analysis via WB experiment indicated that c.369 C >G reduced the protein expression level of LSS.Analysis of protein stability prediction showed a destabilizing for LSS caused by the variant c.401T>G.This study is the frst study in Asia to date. These findings expanded the variantal spectrum of LSS-related APMR4 and revealed the potential pathogenic mechanism of LSS gene variants.